In Vitro and In Vivo Anti-tumoral Effects of the Flavonoid Apigenin in Malignant Mesothelioma - Masuelli, Laura; Benvenuto, Monica; Mattera, Rosanna; Di Stefano, Enrica; Zago, Erika; Taffera, Gloria; Tresoldi, Ilaria; Giganti, Maria Gabriella; Frajese, Giovanni Vanni; Berardi, Ginevra; Modesti, Andrea; Bei, Roberto (Frontiers in Pharmacology, 2017)
Malignant mesothelioma (MM) is a tumor arising from mesothelium. MM patients’ survival is poor. The polyphenol 4’,5,7,-trihydroxyflavone (Apigenin (API) is a “multifunctional drug”. Several studies have demonstrated API anti-tumoral effects. However, little is known on the in vitro and in vivo anti-tumoral effects of API in MM. Thus, we analyzed the in vitro effects of API on cell proliferation, cell cycle regulation, pro-survival signaling pathways, apoptosis, and autophagy of human and mouse MM cells. We evaluated the in vivo anti-tumor activities of API in mice transplanted with MM #40a cells forming ascites. API inhibited in vitro MM cells survival, increased reactive oxygen species intracellular production and induced DNA damage. API activated apoptosis but not autophagy. API-induced apoptosis was sustained by the increase of Bax/Bcl-2 ratio, increase of p53 expression, activation of both caspase 9 and caspase 8, cleavage of PARP-1, and increase of the percentage of cells in subG1 phase. API treatment affected the phosphorylation of ERK1/2, JNK and p38 MAPKs in a cell-type specific manner, inhibited AKT phosphorylation, decreased c-Jun expression and phosphorylation, and inhibited NF-κB nuclear translocation. Intraperitoneal administration of API increased the median survival of C57BL/6 mice intraperitoneally transplanted with #40a cells and reduced the risk of tumor growth. Our findings may have important implications for the design of MM treatment using API.